THE USE OF INDONESIAN FIRST-SINGULAR-PRONOUNS BY STUDENTS INTERACTING WITH TEACHERS: SAYA OR AKU? - Elisabet Titik Murtisari; Dea Devina Fabrian; Rosyana Diva Lolyta; Desy Rizki Lukitasari; Venny Christayani Rahardjono (Kajian Linguistik dan Sastra, 2019)
This study examines students’ selection of the pronouns of saya and aku (“I”) when speaking with their teachers. Saya is traditionally prescribed to be the standard form to show politeness and respect, but it has been observed recently that some students have started to use the more informal version aku in the capital city of Jakarta. Therefore, this study aims to describe the use of the pronouns and their accompanying reasons by high school students in a small city in Central Java. This study is crucial to understand student-teacher relationships in the modern Indonesian society. Involving 247 students from a state school and a christian private one in the city of  Salatiga,  the research indicates a move towards the use of the more informal self-reference aku towards teachers although the degree varies depending on the school.  It also suggests that there is a possible shift from “negative/independence” to “positive/solidarity” politeness among senior high students in their interaction with their teachers.